A descriptive analysis of human milk dispensed by the Leipzig Donor Human Milk Bank for neonates between 2012 and 2019 - Siziba, Linda P.; Baier, Caroline; Pütz, Elisabeth; Ascherl, Rudolf; Wendt, Thomas; Thome, Ulrich H.; Gebauer, Corinna; Genuneit, Jon (Frontiers in Nutrition, 2023)
Background: Human milk banking has become an important aspect of Nutritional medicine. It is not just about the provision of mother’s own milk (MOM) or donor human milk (DHM) in the hospital, but also a strategy to encourage breastfeeding in the clinical setting and beyond. Objective: To describe the feeding patterns of hospitalised infants including human milk dispensed by the Leipzig Donor Human Milk Bank (LMB). Design: A descriptive analysis of daily data on milk feeds dispensed by LMB for hospitalised infants distinguishing between MOM or DHM, either fresh or frozen, and raw/pasteurised milk from 2012-2019. Results: We included 2562 infants with median hospitalisation of 23 days, for whom human milk was dispensed on median 76% of those days and other nutrition on the remaining days. Raw MOM and raw DHM comprised 52% and 8% of the dispensed milk, respectively. Dispensing exclusive DHM instead of MOM for at least one full day was required in 55% of the infants, mostly at the beginning but also later during hospitalisation. Exclusive raw DHM was dispensed on at least one day for 37% of the infants, in different birthweight strata <1000g: 10%, 1000-1500g: 11%, 1500-2500g: 13% and >2500g: 3%. At discharge, MOM was dispensed for more than 60% of the infants. Conclusion: During an infant’s hospital stay, LMB dispenses various human milk feeds with interspersed DHM resulting in complex intra-individual time-variant feeding patterns. LMB dispenses raw MOM and especially raw DHM with the intention to retain the properties of human milk unlike a diet containing pasteurised DHM and/or formula. Although raw DHM comprises a small percentage of all dispensed milk, raw DHM is dispensed for a substantial portion of infants. Our results document that dispensing raw DHM, is possible in routine settings.